The relationship between fear of negative evaluation, social anxiety disorder and distress among Icelandic undergraduate in a virtual reality environment - Karen Söring Ragnarsdóttir 1995- (2019)
The aim in the present study was to examine the relationship between social anxiety disorder (SAD), fear of negative evaluation (FNE) and distress among students giving a presentation in front of virtual audience in a virtual reality (VR) environment. The participants (N = 81) were undergraduate students, 62 women and 19 men at Reykjavik University. They began by completing questionnaires assessing SAD, FNE and distress. It was hypothesized that students with higher levels of SAD would report higher levels of FNE, students with higher levels of SAD and FNE would report higher levels of distress, and that the relationship between SAD and distress would be mediated by FNE. Repeated measure ANOVA analyses of variance using the general linear model (GLM) supported all the hypotheses. Students with higher levels of SAD reported higher levels of FNE, students with higher levels of SAD and FNE reported higher levels of distress both during the waiting and the presentation period, and the relationship between SAD and distress was fully mediated by FNE. As far as we are aware, this is the first study to show this relationship. The findings indicate that interventions aimed at reducing FNE among individuals with high levels of SAD may be effective in reducing the impact on distress of presenting in front of an audience. Keywords: Social Anxiety Disorder, Fear of Negative Evaluation, Distress, Virtual Reality Markmið þessarra rannsókna var að skoða sambandið á milli félagskvíða, ótta við neikvætt mat (FNE), og kvíða, hjá háskólanemum sem héldu kynningu fyrir framan sýndarveruleikafólk í sýndarveruleika umhverfi. Þátttakendurnir (N = 81) voru nemar, 62 konur og 19 karlar, í háskólanum í Reykjavík. Þeir byrjuðu á að svara sjálfsmatskvörðum sem spurðu um félagskvíða og FNE, og kvíða. Við ályktuðum að nemendur með hærra stig af félagskvíða myndu hafa hærra stig af FNE, nemendur með hærra stig af félagskvíða og FNE myndu hafa hærra stig af kvíða í, og sambandið á milli félagskvíða og kvíða í væri miðlað af FNE. Endurtekin ...